Caracterización del aceite esencial de tzintzo (tagetes minuta), en función a la composición química, capacidad antioxidante y actividad antimicrobiana. - Medina Jiménez, Carolina Alexandra (2023)
The present work had the purpose of characterizing the essential oil of tzintzo (Tagetes minuta), based on the chemical composition, antioxidant capacity and antimicrobial activity. The experimental design was established by the Desing Expert software, in which 17 experimental runs were determined, considering the independent variables of time (60, 105 and 150 min) and plant material/distilled water ratio (1:3, 1:4, 1 :5). In the optimized one, a time of 150 min and 1:5 of the mass (g)/solvent (L) ratio was obtained, the mixture of steam-water - essential oil was condensed in a refrigerant system, in a separator by difference of densities. hydrosol is removed and at the end of the process the essential oil is removed and bottled in amber glass bottles; the yield value 0.7891% was higher than the predicted 0.7114%.